2013
DOI: 10.1097/spv.0b013e318285ba53
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Prophylaxis for Urinary Tract Infection After Midurethral Sling

Abstract: A short (3-day) course of nitrofurantoin after outpatient sling surgery significantly reduces the incidence of postoperative bladder infection in the first 6 weeks after sling surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 21 publications
1
21
1
1
Order By: Relevance
“…Anger et al 31 reported an absolute UTI rate of 34% in the 3 months following a sling procedure, Jackson et al 32 reported a UTI rate of 32% in women undergoing outpatient sling procedures (with or without outpatient pelvic reconstructive procedures) who were not treated with postoperative prophylactic antibiotics.…”
Section: Resultsmentioning
confidence: 99%
“…Anger et al 31 reported an absolute UTI rate of 34% in the 3 months following a sling procedure, Jackson et al 32 reported a UTI rate of 32% in women undergoing outpatient sling procedures (with or without outpatient pelvic reconstructive procedures) who were not treated with postoperative prophylactic antibiotics.…”
Section: Resultsmentioning
confidence: 99%
“…4 In the field of obstetrics and gynecology, UTI is one of the most common complications of pelvic reconstructive surgery, as is urinary retention. 5,[7][8][9][10][11][12][13][14][15] Urinary retention occurs in up to 50% of women undergoing pelvic floor surgery. 5,[7][8][9][10][11][12][13][14][15] Urinary retention occurs in up to 50% of women undergoing pelvic floor surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies included women who had vaginal surgery concomitantly with MUS. Harmanli et al, Ghezzi et al, and Swartz et al examined women with MUS alone.…”
Section: Resultsmentioning
confidence: 99%
“…Harmanli et al, Ghezzi et al, and Swartz et al examined women with MUS alone. Among studies of women with vaginal surgery concomitant with MUS, Dieter et al, Hampton et al, and Jackson et al analyzed UTI post‐MUS as a separate group; however, the studies were not powered to analyze differences in the primary outcome stratified by surgery type. Five studies included both retropubic and transobturator MUS .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation